Internet connectivity disruption in Ethiopia (Ethiopia) - Voidly (2026)
CRITICAL severity disruption detected in Ethiopia. Confidence: 75%. Data sourced from IODA.
Network Disruption Incident ID: ET-2026-0054
Keywords: internet disruption; ET; disruption; critical